A Cross-National Investigation of Hallucination-Like Experiences in 10 Countries: The E-CLECTIC Study. (1st February 2019) - Siddi, Sara; Ochoa, Susana; Laroi, Frank; Cella, Matteo; Raballo, Andrea; Saldivia, Sandra; Quijada, Yanet; Laloyaux, Julien; Rocha, Nuno Barbosa; Lincoln, Tania M; Schlier, Björn; Ntouros, Evangelos; et al.
Abstract: Hallucination-like experiences (HLEs) are typically defined as sensory perceptions in the absence of external stimuli. Multidimensional tools, able to assess different facets of HLEs, are helpful for a better characterization of hallucination proneness and to investigate the cross-national variation in the frequencies of HLEs. The current study set out to establish the validity, factor structure, and measurement invariance of the Launay-Slade Hallucinations Scale-Extended (LSHS-E), a tool to assess HLEs. A total of 4419 respondents from 10 countries were enrolled. Network analyses between the LSHS-E and the 3 dimensions of the Community Assessment of Psychic Experiences (CAPE) were performed to assess convergent and divergent validity of the LSHS-E. Confirmatory factor analysis was used to test its measurement invariance. The best fit was a 4-factor model, which proved invariant by country and clinical status, indicating cross-national stability of the hallucination-proneness construct. Among the different components of hallucination-proneness, auditory-visual HLEs had the strongest association with the positive dimension of the CAPE, compared with the depression and negative dimensions. Participants who reported a diagnosis of a mental disorder scored higher on the 4 LSHS-E factors. Small effect size differences by country were found in the scores of the 4 LSHS-E factors even after taking into account the role of socio-demographic and clinical variables. Due to its good psychometric properties, the LSHS-E is a strong candidate tool for large investigations of HLEs.